Pragmatism and feasibility: A qualitative study of experiences implementing and upgrading care in geriatric emergency departments - Anita Chary; Annika Bhananker; Vivian Ramont; Lauren Southerland; Aanand Naik; Kyler Godwin; Maura Kennedy (Journal of the American College of Emergency Physicians Open, 2024)
Abstract Objectives Implementation and sustainability of new care processes in emergency departments (EDs) is difficult. We describe experiences of implementing geriatric care processes in EDs that upgraded their accreditation level for the Geriatric Emergency Department Accreditation (GEDA) program. These EDs can provide a model for adopting and sustaining guidelines for evidence‐based geriatric care. Methods We performed qualitative interviews with geriatric ED nurse and physician leaders overseeing their ED's geriatric accreditation processes. The interview guide was based on the Consolidated Framework for Implementation Research (CFIR), a framework consisting of a comprehensive set of factors that impact implementation of evidence‐based interventions. We used inductive analysis to elucidate key themes from interviews and deductive analysis to map themes onto CFIR constructs. Results Clinician leaders from 15 of 19 EDs that upgraded accreditation status by March 1, 2023 participated in interviews. Motivations to upgrade accreditation level centered on improving patient care (73%) and achieving recognition (56%). Rationales for choosing specific care processes were more commonly related to feasibility (40%) and ability to integrate the processes into the electronic health record (33%) than to site‐specific patient needs (20%). Several common experiences in implementation were identified: (1) financing from the larger health system or philanthropy was crucial; (2) translating the Geriatric ED Guidelines into clinical practice was challenging for clinician leaders; (3) motivational barriers existed among frontline ED staff; (4) longitudinal staff education was needed given frontline ED staff attrition and turnover; and (5) the electronic health record facilitated implementation of geriatric screenings. Conclusions Geriatric ED accreditation involves significant time, resource allocation, and longitudinal staff commitment. EDs pursuing geriatric accreditation balance aspirations to improve patient care with resource availability to implement new care processes and competing priorities.